A rare case of intracytoplasmic mucin‐rich nasopharyngeal carcinoma. Issue 6 (31st January 2022) - Yamaguchi, Yohei; Odate, Toru; Nakazawa, Kumiko; Oishi, Naoki; Mochizuki, Kunio; Shimizu, Tatsuya; Horiuchi, Kiwako; Ishii, Hiroki; Sakurai, Daiju; Kondo, Tetsuo
Abstract: Nasopharyngeal carcinoma (NPC) is an Epstein–Barr virus (EBV)‐associated tumor with a high incidence in Asian countries. NPC is a type of squamous cell carcinoma originating from the nasopharyngeal mucosa. Although rare, NPCs show some uncommon histologic variants; these variations remain to be understood. We described the cytologic characteristics of a rare NPC variant with abundant intracytoplasmic mucin. A 37‐year‐old Japanese man presented to our hospital with bilateral ear discomfort and palpable lymph nodes. Nasopharyngeal biopsy showed tumor cells with abundant intracytoplasmic, Alcian blue‐PAS‐positive mucin. Immunohistochemical analysis demonstrated that the tumor cells were positive for p40 and p53. Epstein–Barr encoding region (EBER) in situ hybridization (ISH) showed EBV infection of the tumor cells. Fluorescence in situ hybridization (FISH) using MAML2 break‐apart probes did not show split signals. Fine needle aspiration biopsy (FNAB) cytology of the metastatic lymph nodes was also performed. Smear samples had a necrotic and inflammatory background with both lymphocyte and neutrophil infiltration. Highly cellular tumor clusters and dispersed cells with naked nuclei were observed. The tumor cells showed a clear cytoplasm with distinct cell borders. Intracytoplasmic mucin pushing the nucleus to the periphery was observed in the scattered tumor cells in a liquid‐based cytology sample. Given these findings, the final diagnosis was advanced nasopharyngeal carcinoma; cisplatin‐based chemoradiation therapy was performed as the first‐line treatment. The tumor recurred 8 months after completing the treatment. The recurrent nasopharyngeal tumor was a typical non‐keratinizing NPC and lacked intracytoplasmic mucin.